2022
DOI: 10.1016/j.buildenv.2021.108742
|View full text |Cite
|
Sign up to set email alerts
|

Profiling office workers based on their self-reported preferences of indoor environmental quality and psychosocial comfort at their workplace during COVID-19

Abstract: Due to the COVID-19 pandemic, a large number of office workers were required to conduct their work from home. Little is known about the indoor environmental quality (IEQ) preferences and psychosocial comfort preferences of staff working from home. Therefore this study aimed to cluster office workers working at home based on their self-reported preferences for IEQ and psychosocial comfort at their most used workspace and to identify these preferences and needs of workers during the COVID-19 pandemic. A question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Moreover, in a study carried out in Egypt among university staff members, high levels of technostress were linked with the female gender and a lousy workplace environment [ 73 ]. Studies comparing women and men show quite a consistent pattern, where women report more stress and more difficulties, worsened by a bad workplace environment [ 26 , 52 , 66 , 72 , 73 , 74 , 75 ] as well as a higher number of hours devoted to child care and home tasks [ 72 ] in comparison with men. Similarly, a Canadian study showed that marginalized workers (women, migrants, and people facing financial hardships) reported lower job security, which was related to lower well-being scores [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in a study carried out in Egypt among university staff members, high levels of technostress were linked with the female gender and a lousy workplace environment [ 73 ]. Studies comparing women and men show quite a consistent pattern, where women report more stress and more difficulties, worsened by a bad workplace environment [ 26 , 52 , 66 , 72 , 73 , 74 , 75 ] as well as a higher number of hours devoted to child care and home tasks [ 72 ] in comparison with men. Similarly, a Canadian study showed that marginalized workers (women, migrants, and people facing financial hardships) reported lower job security, which was related to lower well-being scores [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Table 8 , a list of occupant-related indicators is presented that would be worthy to include and have been suggested in previous studies. 127 , 128 …”
Section: Discussionmentioning
confidence: 99%
“…In other words, to be able to determine the pattern of stressors at the environmental level, clustering occupants based on their preferences is required to first identify the profiles of clusters to better understand how they interact in an indoor environment [25]. So far, a number of studies in which groups of occupants were clustered according to their preferences and needs have shown differences among the profiles of these clusters [26,27].…”
Section: Introductionmentioning
confidence: 99%